2022
DOI: 10.3390/biology11081241
|View full text |Cite
|
Sign up to set email alerts
|

Microglia Are Necessary to Regulate Sleep after an Immune Challenge

Abstract: Microglia play a critical role in the neuroimmune response, but little is known about the role of microglia in sleep following an inflammatory trigger. Nevertheless, decades of research have been predicated on the assumption that an inflammatory trigger increases sleep through microglial activation. We hypothesized that mice (n = 30) with depleted microglia using PLX5622 (PLX) would sleep less following the administration of lipopolysaccharide (LPS) to induce inflammation. Brains were collected and microglial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 116 publications
2
1
0
Order By: Relevance
“…However, in the case that it affected the results, this could indicate that we would have observed a stronger effect on the first day following the withdrawal of the PLX3397. Rowe et al, as well as our group recently obtained similar changes regarding the sleep duration in male mice using the same method (Corsi et al, 2021;Rowe et al, 2022). Similar findings were also recently observed in male and female mice by Liu et al, showing a reduction of stable wakefulness due to an increase in the transitions between wakefulness and NREM sleep using a transgenic model, through ceramide signaling.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, in the case that it affected the results, this could indicate that we would have observed a stronger effect on the first day following the withdrawal of the PLX3397. Rowe et al, as well as our group recently obtained similar changes regarding the sleep duration in male mice using the same method (Corsi et al, 2021;Rowe et al, 2022). Similar findings were also recently observed in male and female mice by Liu et al, showing a reduction of stable wakefulness due to an increase in the transitions between wakefulness and NREM sleep using a transgenic model, through ceramide signaling.…”
Section: Discussionsupporting
confidence: 86%
“…It was also showed by Rowe et al that microglial depletion induced by PLX5622, a colonystimulating factor 1 receptor (CSF1R) inhibitor, could lead to an increased percentage of sleep time during the light period in male mice in the first week following complete microglial depletion (Rowe et al, 2022). Moreover, a study by our group shows that microglia can modulate sleep duration through the fractalkine signaling pathway in male mice (Corsi et al, 2021).…”
Section: Introductionsupporting
confidence: 54%
“…Furthermore, only young animals of one sex were tested, or the sex was left unmentioned ( George et al, 2019 ; Guo et al, 2020 ; Jing et al, 2021 ; Oh et al, 2020 ; Stoll et al, 2023 ; Yang et al, 2018 ; Zhang et al, 2021a ). Although studies of microglia/macrophage repopulation after depletion are fewer, they have shown more consistently beneficial results in models of aging, acute brain injury, Alzheimer’s disease, intracerebral hemorrhage, inflammation, stroke, and parkinsonism ( Barca et al, 2022 ; Coleman Jr. et al, 2020 ; Elmore et al, 2018 ; Henry et al, 2020 ; Johnson et al, 2023 ; Li et al, 2021 ; Li et al, 2022 ; Rice et al, 2017 ; Rowe et al, 2022 ; Willis et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%